Ekbom Syndrome: A Case Report - Pereira, Ana Teresa (2020)
Delusional parasitosis, also known as delusional infestation or Ekbom syndrome, is a somatic type of delusional disorder, usually mono‑symptomatic, in which patients are convinced they are being infested with animal parasites while no objective evidence to support their belief exists. Complaints are usually about skin infestation, but involvement of the gastrointestinal tract has also been described. We describe a case of a 59‑year‑old woman with delusional parasitosis claiming to be infected with Strongyloides stercoralis.